Violêcia contra a mulher: - Silva, Bruna Nicácia Sousa da (Universidade Federal do Tocantins, 2023)
The notification of domestic violence by health professionals contributes to the violence against woman's epidemiological sizing, enabling the development of programmes and specific actions. The number of women who suffer with this problem is increasingly part of the story since the dawn, where they do not possess a special attention and dedicated exclusively to this problematic in our legal system, and in 2006 a coma the creation of Law 11340, also named Maria da Penha Law, to prevent or even minimize the domestic violence within homes. The methodological axes could be distributed primarily with the bibliographical research for knowledge and deepening of the subject, followed by a documentary research performed between the months of December and January 2016 through 2015 of the notifications of cases attended at the Regional Hospital of Araguaina/TO, which provided moments of learning and clarification of doubts. On the context, the aim of this work was to trace the profile of women victims of violence cases reported in 2014 and 2015 as well as to identify the characteristics of that physical violence and its impact.